Managerial Implementation of Madrasah Heads in Adjustment of Curriculum Changes: Study on the Implementation of the Independent Curriculum and the 2013 Curriculum at Madrasah Aliyah Swasta Darrussalam Kampung Banjir Gunung Tua - Nur Holija; Abdurrahman Abdurrahman; Toni Nasution (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2026)
This study aims to describe the implementation of the principal’s managerial functions in adapting to curriculum changes at Madrasah Aliyah Swasta Darussalam Kampung Banjir Gunung Tua. The study focuses on planning, organizing, implementing, and controlling functions in the application of the 2013 Curriculum and the Merdeka Curriculum. A qualitative approach with a case study design was employed. Data were collected through observation, interviews, and documentation. Informants included the principal, vice principal for curriculum, teachers, and education staff. Data were analyzed using the Miles, Huberman, and Saldaña model consisting of data reduction, data display, and conclusion drawing. The findings show that the principal implemented managerial functions through curriculum program planning, teacher task distribution, educator development, academic supervision, and regular learning evaluation. The adaptation strategy involved curriculum team coordination, teacher training, innovative learning development, and strengthening a collaborative organizational culture. Supporting factors include leadership quality, teacher collaboration, curriculum training, and adaptive organizational culture. Inhibiting factors include limited teacher understanding of the Merdeka Curriculum, inadequate facilities, resistance to change, and rapid policy shifts. The study concludes that the success of curriculum change implementation is strongly influenced by the effectiveness of the principal’s managerial functions in managing educational transformation.